MONITORING KUALITAS PERAIRAN SUNGAI KAMPAR DI KAWASAN JEMBATAN PANGKALAN KERINCI UNTUK KEGIATAN BUDIDAYA PERIKANAN PADA KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN, PROVINSI RIAU - Nur Asiah; Yudho Harjoyudanto; Sukendi Sukendi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
Many community activities utilize the Kampar River watershed in the Pangkalan Kerinci Bridge area such as ports, restaurants, cultivation of floating net cages, and sanitary activities. These various activities will affect the water quality there. Therefore monitoring water quality in the region needs to be done to see the quality of its waters which refers to the calculation of the Pollution Index and determine the management of these watersheds to be suitable for aquaculture activities. This research was conducted in November 2017 - February 2018. The survey included measuring water samples and observing the condition of the border and the activities of the community around the river water bodies. Ex situ analysis was conducted at the Laboratory of Ecology and Environmental Management of the Water Faculty of Fisheries and Maritime Affairs, University of Riau. The parameters observed were TSS, DO, COD, BOD, pH, and Total P. Water sample measurements were carried out once at 10 am during sunny weather conditions. There are three sampling points, namely: the area under the Pangkalan Kerinci Bridge (Station I); river wash area 1 (Station II); and river rinse area 2 (Station III). From the results, it is known that overall the Kampar River area around the Pangkalan Kerinci Bridge is in the light-polluted category. Based on the IP value, the condition of the waters in this region can be sorted from high to low polluted that is sequentiallyStation I (2.27), Station II (1.53), and Station III (1.51). It is known that pollutants are organic materials that come from community activities around water bodies. This is evidenced by the high BOD value in water samples. Handling is needed for organic wastes discharged in water bodies to be able to improve the quality of these waters to make them suitable for aquaculture activities.